Drug substitutes − Insights on benefits, risks, detection methods, and management strategies: a systematic review - Bai, Song; Li, Miao; Tang, Shouying; Wan, Suran; Wu, Rong; Chen, Lijun; Wang, Fang; Liu, Shan (Frontiers in Psychiatry, 2025)
The abuse of new psychoactive substances and narcotic drugs as drug substitutes poses a serious threat to public health and safety. This study outlines the effective use and negative abuse of drug substitutes and outlines associated criminal behaviors to help readers understand the potential risks of such substances. By summarizing the technical bottlenecks in the analysis and detection of criminal cases, this study highlights their impact on case discrimination, which in turn can limit or even render policy implementation ineffective. Finally, based on database analysis and the current regulatory system, flexible control strategies were proposed to address the constantly emerging “new” substances, providing a reference for relevant control guidelines to be formulated.